Global Seasonal forecast system version 5 (GloSea5): a high‐resolution seasonal forecast system. (27th June 2014) - MacLachlan, C.; Arribas, A.; Peterson, K. A.; Maidens, A.; Fereday, D.; Scaife, A. A.; Gordon, M.; Vellinga, M.; Williams, A.; Comer, R. E.; Camp, J.; Xavier, P.; et al.
<x xml:space="preserve">Abstract</x> This article describes the UK Met Office Global Seasonal forecast system version 5 (GloSea5). GloSea5 upgrades include an increase in horizontal resolution in the atmosphere (N216–0.7°) and the ocean (0.25°), and implementation of a 3D‐Var assimilation system for ocean and sea‐ice conditions. GloSea5 shows improved year‐to‐year predictions of the major modes of variability. In the Tropics, predictions of the El Niño–Southern Oscillation are improved with reduced errors in the West Pacific. In the Extratropics, GloSea5 shows unprecedented levels of forecast skill and reliability for both the North Atlantic Oscillation and the Arctic Oscillation. We also find useful levels of skill for the western North Pacific Subtropical High which largely determines summer precipitation over East Asia.